1996
DOI: 10.4319/lo.1996.41.3.0451
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic fractionation of ammonium and nitrate during uptake by Skeletonema costatum: Implications for δ15N dynamics under bloom conditions

Abstract: Isotopic fractionation of ammonium (NH,+ ) and nitrate (NO,-) during uptake by phytoplankton was examined in batch culture experiments with the diatom SkeZetonema costatum under nitrogen-enriched conditions (5-100 PM). The fractionation factor (E) for NOJ-uptake by Skeletonema was -9.Of0.7%0 and was concentration-independent. For NH,+, E was more variable and dependent on ambient NH,+ concentration. For NH4+ concentration ranges of 100-50, 50-20, and 20-5 PM, E was -24.6k5.5, -27.2-+ 1.6, and -7.8+3.0%.In thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
151
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(169 citation statements)
references
References 32 publications
(30 reference statements)
13
151
5
Order By: Relevance
“…In the later stages of growth, the reaction may become diffusion limited (R diff oR AMO ) and the isotope effect for diffusion ( 15 e diff ) would dominate. A similar mechanism has been examined for variations in expressed isotopic fractionation during NH 4 þ assimilation by bacteria (Hoch et al, 1992) and marine algae (Pennock et al, 1996), as well as CO 2 uptake by algae (Laws et al, 1997) and plants (O'Leary, 1981). Diffusion of NH 3 in aqueous solution is estimated to have an isotope effect of 20% (Hoch et al, 1992), which is similar to the late-stage 15 e NH3 values we observed.…”
Section: Nitrogen Isotopic Fractionationsupporting
confidence: 57%
“…In the later stages of growth, the reaction may become diffusion limited (R diff oR AMO ) and the isotope effect for diffusion ( 15 e diff ) would dominate. A similar mechanism has been examined for variations in expressed isotopic fractionation during NH 4 þ assimilation by bacteria (Hoch et al, 1992) and marine algae (Pennock et al, 1996), as well as CO 2 uptake by algae (Laws et al, 1997) and plants (O'Leary, 1981). Diffusion of NH 3 in aqueous solution is estimated to have an isotope effect of 20% (Hoch et al, 1992), which is similar to the late-stage 15 e NH3 values we observed.…”
Section: Nitrogen Isotopic Fractionationsupporting
confidence: 57%
“…Ammonification can be abiotic and is just included for completeness. Metal catalysts and isotopic fractionations are taken from the literature (Brunner et al, 2013;Buick, 2007a;Casciotti, 2009;Godfrey and Glass, 2011;Hoch et al, 1992;McCready et al, 1983;Nishizawa et al, 2014;Pennock et al, 1996;Waser et al, 1998;Zerkle et al, 2008;Zhang et al, 2014 Tian et al (2011) and Zahnle (1986), 10. Schoonen & Xu (2001), 11.…”
Section: Discussionmentioning
confidence: 99%
“…Non-quantitative NH 4 + assimilation imparts a fractionation of up to -27‰ when [NH 4 + ] > 20 μM, but the fractionation decreases to -4‰ at lower concentrations (Hoch et al, 1992;Pennock et al, 1996;Waser et al, 1998). Under NH 4 + replete conditions one may thus expect light biomass in underlying sediments (i.e.…”
Section: A Primer On Nitrogen Isotopes In Geological Samplesmentioning
confidence: 99%
“…6b). The extremely low ␦ 15 N bulk value of −4.7‰ at Sancha section may have been produced by green or purple sulfur bacteria participating in ammonia assimilation with a large fractionation (Ohkouchi et al, 2005;Pennock et al, 1996) when upwelling currents were vigorous enough for some ammonia to reach the surface water before being converted to N 2 (Ader et al, 2014) (Fig. 6b).…”
Section: Cambrian Stagementioning
confidence: 99%
“…By contrast, in some regions near zones of water column anoxia with high water-column denitrification and/or anammox rates and complete nitrate assimilation, the ␦ 15 N values of seafloor sediments may be higher (Tesdal et al, 2013). In some modern stratified basins such as the Black Sea, where the O 2 /H 2 S interface exists in the water column instead of in the sediment column, green or purple sulfur bacteria (GSB and PSB) that live principally near the chemocline in the presence of free H 2 S in the photic zone (Ohkouchi et al, 2005) can either participate in N 2 -fixation or assimilate ammonia and/or nitrite with a large and variable fractionation depending on the seawater ammonia concentration (Ohkouchi et al, 2005;Pennock et al, 1996), producing very low ␦ 15 N values. In these anoxic environments, microbial degradation is suggested to retain the initial ␦ 15 N value or only slightly decrease the ␦ 15 N value (Altabet et al, 1999;Higgins et al, 2010;Junium and Arthur, 2007;Möbius et al, 2010).…”
Section: The Marine Nitrogen Cyclementioning
confidence: 99%